Dilly dilly piccalilli : poems for the very young - Livingston, Myra Cohn.; Christelow, Eileen (New York : M.K. McElderry Books, 1989)
A collection of poems about such topics as bugs, weather, food, and the sea, by poets ranging from Robert Louis Stevenson and Walter de la Mare to Gwendolyn Brooks and Arnold Lobel.
Keywords: Children's poetry, American; Children's poetry, English; American poetry -- Collections; English poetry (Collections).